#TITLE_ALTERNATIVE# - IRAWAN (NIM:32211301), DEDY
Reservoir characterization, production forecasting, reserves estimation and classifications are very important in the CBM field development. This study proposes new methods for reservoir characterization and forecasting using production curve type, and proposes new methods to simultaneously estimate radius of investigation and radius of desorption, that have never been done before, using semi-analytical approach. Sensitivity analysis using numerical model is utilized in production type curve development. The proposed method aims to refine the production type curve that commonly used. This method allows the evaluation of CBM well production behavior to be better because it can evaluate the transient period and pseudo steady state period. The desorption radius is estimated using cumulative gas production data. Cumulative water production data, fractional flow curve and sigmoid function are used as a concept of estimating water saturation distribution as a function of time and radius, and this concept was used to estimate radius of investigation. Numerical model was developed to verify proposed radius of desorption and radius of investigation calculation resulted from the analytical method. San Juan Basin coal reservoir properties data were used for conducting the applicability of proposed method. It was successfully showed that this proposed method can simultaneously estimate the radius of desorption and the radius of investigation using gas & water production rate and cumulative data. The results from the proposed method was also compared with the numerical reservoir simulation method.